O1A.1 Pesticide exposure of workers during treatment and re-entry tasks in apple-growing: results from the canepa study in france. (April 2019) - Bureau, Mathilde; Béziat, Béatrix; Duporté, Geoffroy; Lecluse, Yannick; Schwall, Xavier; Bouchart, Valérie; Riou, Gaëlle; Barron, Emmanuelle; Devier, Marie-Hélène; Macary, Francis; Garrigou, Alain; Budzinski, Hélène; et al.
Abstract : Few studies were performed to assess workers' exposure to pesticides in orchards and even less during re-entry activities. However, nearly 40 pesticide treatments per year are carried out in apple-growing especially against fungal diseases, mainly scab. In order to characterize pesticide exposures of farmers in epidemiological studies, we performed a non-controlled field study in 3 regions of France (Normandy, South-West and Rhône-Alpes) in apple orchards during the 2016 and 2017 seasons. We observed the activity of the workers trying to disrupt it as little as possible. Workers' external contamination and their determinants were assessed during 158 working days, corresponding to 31 treatment days (including mixing, spraying and equipment cleaning), 69 re-entry days (including apple hand-thinning, anti-hail net opening and closing tasks) and 58 harvesting days. We performed both detailed observations of work characteristics on the whole day (including an ergonomic approach) and pesticide measurements for dermal contamination during each task (following the OCDE guidelines). Potential dermal exposure was measured with cotton pads placed onto the skin (11 body areas), and cotton gloves or hand rinsing for each task. Captan and dithianon, fungicides representative of pesticide use in apple-growing, were used as markers for exposure. Relative contribution of the different body areas to total exposure was assessed. In addition, to investigate potential sources of contamination, we measured dislodgeable residues in the environment of the workers by analyzing leaf and fruit samples and surfaces of work equipment. Results indicated that workers' dermal exposure was higher during re-entry tasks than treatments and harvests. The median dermal contamination during treatment was 4.03 mg of active ingredients per day, levels ranging from 0.95 mg to 64.19 mg. Most of the contamination was observed on the hands, especially during mixing. We will focus our presentation on levels and main determinants of pesticide exposure during treatment tasks.